PENGARUH E-WOM KONTEN TIKTOK TERHADAP MINAT KUNJUNGAN DI SETU PATOK KABUPATEN CIREBON - Spika Yusmiyati; Abdul Khalim (Jurnal Cakrawala Ilmiah, 2025)
Setu Patok is a lake or reservoir whose construction began in 1921 and was completed in 1925 by the Dutch. It is located at the coordinates 6°47'04.9"S 108°34'06.7"E in Setu Patok Village, Mundu Subdistrict, Cirebon Regency, West Java Province, Indonesia, with an area of 4.25 square kilometers. Setu Patok gained attention through Electronic Word Of Mouth (EWOM), first published on the TikTok application. The occurrence of Electronic Word Of Mouth (EWOM) at Setu Patok was due to the receding and drying up of water, revealing the bottom of Setu Patok Dam. The receding water transformed Setu Patok, which was initially filled with water, into a grassland resembling a savanna. This created a beautiful landscape with a natural phenomenon, which is the subject of this study. TikTok itself is an application that first made Setu Patok a subject of Electronic Word Of Mouth (EWOM). TikTok is a popular social media platform that allows users to create and share short-form videos. The application is widely liked because of its interesting and creative content. With its large user base and diverse content, TikTok has become one of the most popular social media platforms for content creation and consumption, especially among young people. TikTok was the medium for spreading information about Setu Patok, which will be studied. This research aims to determine the effect of viral marketing or Electronic Word Of Mouth (EWOM) on tourist interest in visiting Setu Patok, Cirebon Regency. In this study, the author uses quantitative research methods, supported by three data collection techniques: observation, questionnaires, and documentation. Using simple linear regression analysis, the results of this study show that viral marketing or Electronic Word Of Mouth (EWOM) can influence tourist visits to Setu Patok. In the simple linear regression analysis that has been conducted, the result shows a Constant (α) = 3.935, meaning that if the electronic word of mouth (EWOM) content on TikTok (X) is present, the interest in visiting is 3.935. The regression direction coefficient / β (X) = 0.744 (positive value) means that if the electronic word of mouth (EWOM) content on TikTok (X) increases by one unit, the interest in visiting will also increase by 0.744. Therefore, Electronic Word of Mouth (EWOM) content on TikTok has a positive and significant effect on the interest in visiting Setu Patok, Cirebon Regency.